2023
DOI: 10.1002/2211-5463.13601
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of resveratrol on the ethanol‐induced disruption of retinogenesis in pluripotent stem cell‐derived organoids

Abstract: Prenatal alcohol exposure‐induced fetal alcohol syndrome (FAS) can lead to serious maldevelopment in many organ systems, including the eyes. In the present study, the effects of alcohol exposure on early development of the human retina and the therapeutic effects of resveratrol on alcohol‐induced neural retinal damage were observed for the first time in an in vitro retinal organoid model. We report that the number of proliferating and apoptotic cells decreased and increased, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…A recent study has shown that resveratrol can play a protective role in the neural retina from alcohol exposure by activating the PI3K/AKT signaling pathway. Additionally, it was detected, that the expression levels of RELN, FGFR2, MET, and PIK3AP1 were upregulated with the treatment of RES in comparisons (Li et al 2023). In our study, we found that RELN mRNA levels increased under resveratrol treatment.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study has shown that resveratrol can play a protective role in the neural retina from alcohol exposure by activating the PI3K/AKT signaling pathway. Additionally, it was detected, that the expression levels of RELN, FGFR2, MET, and PIK3AP1 were upregulated with the treatment of RES in comparisons (Li et al 2023). In our study, we found that RELN mRNA levels increased under resveratrol treatment.…”
Section: Discussionmentioning
confidence: 94%